Correction: Qamar et al. Treatment of Peripheral Artery Disease Using Injectable Biomaterials and Drug-Coated Balloons: Safety and Efficacy Perspective. Pharmaceutics 2023, 15, 1813 - Safi Ur Rehman Qamar; Lemana Spahić; Leo Benolić; Marko Zivanovic; Nenad Filipović (MDPI AG, 2023)
There was an error in the original publication [...]